Teaching by legal competences - Olano García, Hernán Alejandro (2007)
The author presents a proposal of education by specific competitions in Law within the project Tuning Latin America, to do so, with the restricted existing sources of intelligence, develops the history of the process and presents in addition some considerations to us on the formation by competitions and the formative project, or program of Colombian Constitutional Law, in which includes four of the European Tuning competitions for the development of the formative route of any legal subject.